2014
DOI: 10.1007/s11250-014-0579-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex and genotype on growth performance, feed efficiency, and carcass traits of local sheep group Pantaneiro and Texel or Santa Inês crossbred finished on feedlot

Abstract: This study aimed to assess and compare the growth performance, feed efficiency, and carcass traits of Pantaneiro sheep and their Texel and Santa Inês crossbreds. Ninety-six lambs, fifty-one males, and forty-five females, with a mean weaning weight of 15.21 ± 1.25 kg and 78 ± 13 days of age, were slaughtered at a 32-kg body weight. The results showed better production efficiency from males compared with females. Texel-crossed lambs had a better growth performance than the other genotypes. The Texel × Pantaneiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
2
16
2
3
Order By: Relevance
“…O experimento foi conduzido no confinamento do Centro de Pesquisa de Ovinos (CPO) da Universidade Federal da Grande Dourados, localizada no município de Dourados-MS. Foram utilizados 24 cordeiros machos não castrados, com idade média de 90 dias e peso médio de 20,02 ± 1,5 kg, sendo estes animais pertencentes a um grupo de ovinos naturalizados do estado de Mato Grosso do Sul, denominados "Pantaneiros" (VARGAS JUNIOR et al, 2014). Os animais foram alojados em baias individuais com 2m 2 , providas de comedouro e bebedouro tipo nipple e dispostas em área coberta.…”
Section: Methodsunclassified
“…O experimento foi conduzido no confinamento do Centro de Pesquisa de Ovinos (CPO) da Universidade Federal da Grande Dourados, localizada no município de Dourados-MS. Foram utilizados 24 cordeiros machos não castrados, com idade média de 90 dias e peso médio de 20,02 ± 1,5 kg, sendo estes animais pertencentes a um grupo de ovinos naturalizados do estado de Mato Grosso do Sul, denominados "Pantaneiros" (VARGAS JUNIOR et al, 2014). Os animais foram alojados em baias individuais com 2m 2 , providas de comedouro e bebedouro tipo nipple e dispostas em área coberta.…”
Section: Methodsunclassified
“…Carcass yield found here were relative low for all genetic groups. Other studies have shown carcass yield ranging from 37% to 50% (Vargas Junior et al 2014) in crossbred lambs slaughtered at approximately the same weight (30kg). The former found that carcass yield improve with increased concentrate in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also point to this manner of using local genetic resources. Vargas Junior et al (2014; showed that Texel x Pantaneiro crosses were more efficient with a better feedlot performance, higher ribeye muscle area and better carcass characteristics with an adequate amount of fat cover. As no difference in production was seen between specialized and local breeds, probably there is a lack in environment adaptability when changing Santa Inês dams for those of specialized breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment followed the guidelines stated in the Guide for the Care and Use of Agricultural Animals in Research and Teaching, and was performed as described by Vargas Junior et al (2014). A total of 96 weaned lambs with a mean weight of 15.21 ± 1.25 kg and an age of 78 ± 13 d were used.…”
Section: Animals and Dietmentioning
confidence: 99%